Stereopsidales--a new order of mushroom-forming fungi. - Elisabet Sjökvist (Public Library of Science (PLoS), 2014)
One new order, one new family, and one new combination are presented, as the result of molecular phylogenetic analyses. The new order Stereopsidales and the new family Stereopsidaceae are described incorporating Stereopsis radicans and S. globosa, formerly Clavulicium globosum. We show that not only do these species represent an old overlooked lineage, but both species harbor cryptic diversity. In addition, a third species, C. macounii, appears as a plausible sister to the new lineage, but there is conflict in the data. All specimens of S. radicans and S. globosa analysed here are from the South and Central Americas; several records of S. radicans have been made also from tropical Asia. We expect the true diversity in this group to be a lot higher than presented in this paper. Stereopsis radicans was formerly included in Polyporales, but a placement within that order is rejected by our data through SH tests. The dataset consisted of four nuclear markers: rpb2, tef1, LSU and SSU, each of which was analysed separately using maximum likelihood and Bayesian inference. Recombination detection tests indicate no plausible recombinations. The potential of S. radicans, S. globosa and C. macounii being amphitallic is briefly discussed.